Morpho-genetic Characterization of Traditional Aromatic Tulaipanji Rice of North Bengal, India - Ghosh, Mrityunjay; Mondal, G.; Das, B.; Ghose, T. K. (International Journal of Bio-resource and Stress Management, 2018)
Tulaipanji is a non-Basmati type aromatic rice landrace of old alluvial region of North Bengal in eastern part of.India, which is presently cultivated in about 7,000 ha. land with production of 14,000–15,000 tonnes paddy every year. With a view to develop the phenotypic and genetic database of the unique variety, its agro-morphological characterization was done at ‘C’ Block Farm, B.C.K.V., Kalyani, West Bengal during kharif (wet) season of 2011, 2012 and 2013 following the DUS test guidelines of Protection of Plant Varieties and Farmers’ Rights Authority (PPV&FRA). The variety had late heading (110-115 days) and late maturity (140–150 days), which produced long statured plants (125-135 cm height) with no anthocyanin colouration on leaf blade, sheath, nodes and internodes. The flower was bi-sexual including six yellow coloured anthers, and an ovary with white or yellowish-white feathery stigma. The lemma and palea were straw in colour with long awns (mean length 17.3 mm), and the grains were short in length (7.5 mm) with low test weight (15.6 g). The kernels were medium-slender (length 5.27 mm and width 1.91 mm) in shape and white in colour, which had low amylose content (17.2%), medium gelatinization temperature (alkali value 4.3) and medium aroma. 23 simple sequence repeat (SSR) markers were used for DNA amplification profile to develop molecular base-pair length database of Tulaipanji rice against non-aromatic international check variety IR 36 in the study. Among them, one marker (RM 182) recorded similar molecular weights for both the varieties, while two markers (RM 207 and RM 339) made greater genetic distances between Tulaipanji and IR 36 (75.82 vs. 128.48 bp and 182.76 vs. 143.09 bp, respectively).